2015
DOI: 10.1007/s11250-015-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of smallholder pig breeding practices within a rural commune of North Central Vietnam

Abstract: This case study focused on a pig production system in a rural area of North Central Vietnam, with a focus on describing household pig breeding practices and estimating herd demographic parameters, particularly on reproduction. One hundred five households undertaking small-scale piglet production were surveyed, with information gathered on 3268 individual pigs. Pig keeping contributed variably to the overall household livelihood portfolio, with female household members as the main decision makers, contributors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The surveys were conducted from 5 th January to 29 th January, 2020 to get data with two levels which were a household-level and a farm-level survey, which were presented in case of ruminant livestock (Lesnoff et al, 2010) and in case of swine production (Ieda et al, 2015). The survey was conducted in the local language (Vietnamese).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surveys were conducted from 5 th January to 29 th January, 2020 to get data with two levels which were a household-level and a farm-level survey, which were presented in case of ruminant livestock (Lesnoff et al, 2010) and in case of swine production (Ieda et al, 2015). The survey was conducted in the local language (Vietnamese).…”
Section: Data Collectionmentioning
confidence: 99%
“…There are significantly different knowledge gaps between swine raisers and also between the characteristics of smallholders about various swine production systems, from both social-economic and productivity perspective (Ieda et al, 2015). Social demographic characteristics such as age, gender, family member, formal education, experience, and constraints were recorded as factors affecting animal production (Ibrahim et al, 2013;Odhiambo et al, 2019;Phiri, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that some pigs are very susceptible to ASF, while others are asymptomatic carriers of the virus, despite infection with similar virus genotypes [ 7 , 25 , 27 , 28 ]. The locally-adapted pigs are favorites among smallholder farmers in many parts of the world [ 29 , 30 ], including in South-western Kenya, where ASFV persistence in tissues of apparently healthy pigs has been reported [ 7 ]. The level of protection has been attributed to antibody-dependent cytotoxicity that offers limited protection only against homologous ASFV challenge, delaying the onset of clinical signs and viremia [ 31 – 33 ].…”
Section: Introductionmentioning
confidence: 99%